2018
DOI: 10.1080/01443615.2018.1437718
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of attitudes towards female genital mutilation (FGM) in men and women accessing FGM clinical services in London: a pilot study

Abstract: This pilot study researched the attitudes towards and the knowledge of female genital mutilation (FGM) in adult women with FGM and their partners. The participant population consisted of English-speaking women and men over 18 years old attending specialist FGM clinics in two London hospitals. The participants completed a questionnaire on the attitudes and the knowledge of FGM, which were adapted with permission from the United Nations Children's Fund and the United States Agency for International Development h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…14 In the UK also, there are indications that there is broad opposition to circumcision of girls among people from practicing countries. 15,16 That cultural change might be happening on a large scale in Europe is supported by findings in a study commissioned by the European Commission. An analysis of FGM court cases in Europe showed that fewer than 50 cases of suspected illegal FGM have reached criminal courts, and out of those 50, more than 30 took place in France in the 1980s.…”
Section: Circumcision Of Girls Residing In Europementioning
confidence: 93%
See 2 more Smart Citations
“…14 In the UK also, there are indications that there is broad opposition to circumcision of girls among people from practicing countries. 15,16 That cultural change might be happening on a large scale in Europe is supported by findings in a study commissioned by the European Commission. An analysis of FGM court cases in Europe showed that fewer than 50 cases of suspected illegal FGM have reached criminal courts, and out of those 50, more than 30 took place in France in the 1980s.…”
Section: Circumcision Of Girls Residing In Europementioning
confidence: 93%
“…A growing number of studies show that migration seems to be a key factor for change when it comes to attitudes and practices regarding circumcision of girls among Africans in Europe. [7][8][9][10][11][12][13][14][15][16] Some 200,000 people who were born in Africa live in Sweden. The biggest community is the Somalipersons born in Somalia amount to more than 66,000.…”
Section: Circumcision Of Girls Residing In Europementioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, they now provide two estimates, for low-risk (assuming total cultural change and no circumcision of second-generation migrants) and high-risk scenarios (accounting for no cultural change) (28). Large scale attitude changes towards FGC are reported in Sweden, Germany, Switzerland, and the UK among migrants (29)(30)(31). In a qualitative study from 2009, Swedish-Eritreans and Swedish-Somalis referred to FGC as a "brutal practice" (32), which suggests the low-risk scenario estimations might be representative.…”
Section: Accepted Articlementioning
confidence: 99%
“…If there is any reason to suspect this abuse has occurred, a sensitive enquiry should be made asking if individuals are aware of the custom of genital cutting in some communities and whether this is something they have experienced [19]. Hospital Trusts have policies in place regarding female genital mutilation, and clinicians will need to be able to make appropriate enquiries assessing parental attitudes to this, and to ensure there is an awareness of UK law [20].…”
Section: Female Genital Cuttingmentioning
confidence: 99%